The Influence of Literacy and Read Aloud Activities on the Early Childhood Education Students’ Receptive Language Skills - Eko Priyantini, Lely Diah; Yusuf, Amin (Journal of Primary Education, 2020)
Stimulation on language development aspects is greatly needed since humans’ life may not be separated from language use and acquisition. This research aims at examining the influence of literacy and read aloud activities on the early childhood education students’ receptive language skills. This research is a correlational quantitative study conducted with a survey approach. The research population was the students of Early Childhood Education Institutions in South Purwokerto District, Banyumas Regency. There were 54 Early Childhood Education Institutions in South Purwokerto District divided into 7 groups/clusters. The sampling of this research was conducted by using the Slovin’s formula with the total samples of 115 students of Early Childhood Education Institutions. The data was collected through observation and then descriptively analyzed in percentages using multiple regression analysis supported with SPSS 23.0. The research results showed that literacy activities influenced the Early Childhood Education students’ receptive language skills with the t-count value of 6.620 at the significance of 0.000. Read aloud activities also influenced the Early Childhood Education students’ receptive language skills with the t-count value of 8.066 at the significance of 0.000. Literacy and read aloud activities significantly influenced the Early Childhood Education students’ receptive language skills with the f-count value of 70.386 at the significance of 0.000 and the total influence of 55.5%. Thus, it is suggested that literacy and read aloud activities should be continuously made to improve the Early Childhood Education students’ receptive language skills.